Clinicopathological findings of a mitochondrial encephalopathy, lactic acidosis, and stroke‐like episodes/Leigh syndrome overlap patient with a novel m.3482A>G mutation in MT‐ND1. Issue 1 (9th December 2020) - Hayashi, Yuichi; Iwasaki, Yasushi; Yoshikura, Nobuaki; Yamada, Megumi; Kimura, Akio; Inuzuka, Takashi; Miyahara, Hiroaki; Goto, Yuichi; Nishino, Ichizo; Yoshida, Mari; Shimohata, Takayoshi
Abstract : We report clinicopathological findings of a patient with mitochondrial encephalopathy, lactic acidosis, and stroke‐like episodes/Leigh syndrome (MELAS/LS) associated with a novel m.3482A>G mutation in MT‐ND1 . A 41‐year‐old woman had experienced multiple stroke‐like episodes since age 16. She developed akinetic mutism two months before admission to our hospital. Neurological examination revealed akinetic mutism, bilateral deafness, and muscular atrophy. Cerebrospinal fluid tests revealed elevated pyruvate and lactate levels. Fluid‐attenuated inversion recovery images on magnetic resonance imaging showed hyperintense areas in the right frontal and both sides of temporal and occipital lobes, both sides of the striatum, and the midbrain. Muscle biopsy revealed strongly succinate dehydrogenase‐reactive blood vessels. L‐arginine therapy improved her consciousness and prevented further stroke‐like episodes. However, she died from aspiration pneumonia. Postmortem autopsy revealed scattered infarct‐like lesions with cavitation in the cerebral cortex and necrotic lesions in the striatum and midbrain. The patient was pathologically confirmed as having MELAS/LS based on two characteristic clinicopathological findings: presenting MELAS/LS overlap phenotype and effectiveness of L‐arginine treatment.